التّناص الدّينيّ في شعر أبي مسلم البهلانيّ: دارسة تحليليّة: The religious intertextuality in the poetry of Abū Muslim al-Bahlānī: an Analytical study - Ahmad, Muhammad Anwar; Albarashdi, Ahmed Nasser Habib (AL-HIKMAH: INTERNATIONAL JOURNAL OF ISLAMIC STUDIES AND HUMAN SCIENCES, 2023)
ملخص البحث يُعدّ أبو مسلم البهلانيّ من أكثر الشعراء العمانيّين حضورا في مخيلة الكثير من العمانيّين، لقد كان الشعر عند أبي مسلم وسيلة لتوصيل رسائله الدينيّة والسياسيّة والاجتماعيّة والثقافيّة، وكان همه إيصال رسالة للأمة العربيّة والإسلاميّة عامّة بضرورة التّمسك بالدّين وتعاليمه وبالوحدة ونبذ الشقاق. والملاحظ في نتاج أبي مسلم الشعريّ أنه كثيرا ما يستلهم مادته من النّصوص الدينيّة: القرآن الكريم والحديث النبويّ. استدعاء الشاعر هذه النّصوص واستثمارها في شعره يعدّ من مظاهر التّناص؛ فيأتي هذا البحث الكشف عن التّناص الدينيّ في شعر أبي مسلم البهلانيّ وبيان فوائد توظيفه التّناص في شعره. ويتبنّى البحث المنهج التحليليّ وذلك من خلال دراسة وتحليل الأبيات الشعريّة التي تمّ توظيف التّناص فيها إضافة إلى تحليل أسباب وأسرار توظيفه. وتكمن أهميّة البحث في إبراز الشعر العربيّ الحديث الملتزم إضافة إلى اهتمامه بأثر القرآن الكريم والحديث النبويّ في الشعر الإسلاميّ. وقد توصّل البحث إلى نتائج مهمّة ومن أبرزها أن التّناص أداة فاعلة من أدوات الشّاعر لتقويّة الدّلالة، وتحسين الألفاظ، وإثراء التّجربة الشعريّة، وإخراج صور جديدة مستلهمة من الواقع. ABSTRACT Abū Muslim al-Bahlānī is considered one of the most present Omani poets in the imagination of many Omanis. For Abū Muslim, poetry was a means of conveying his religious, political, social, and cultural messages, and his concern was to deliver a message to the Arab and Islamic nation in general of the necessity of adhering to religion and its teachings, unity and rejecting discord. What is noticeable in Abū Muslim’s poetic works is that he often draws inspiration from religious texts: the Holy Qur’an and the Prophet’s Hadith. The poet’s summoning of these texts and investing them in his poetry is a manifestation of intertextuality. This research aims to reveal religious intertextuality in the poetry of Abū Muslim al- Bahlānī and explain the benefits and secrets of employing intertextuality in his poetry. The research adopts the analytical approach by studying and analyzing poetic texts in which intertextuality was used, in addition to analyzing the reasons and secrets of its use. The importance of the research lies in highlighting committed modern Arabic poetry, in addition to its interest in the impact of the Holy Qur’an and the Prophet’s Hadith on Islamic poetry. The research found that intertextuality is an effective tool for the poet to strengthen meaning, improve wording, enrich the poetic experience, and produce new images inspired by reality.